A STUDY ABOUT STATUS OF SOCIAL JUSTICE IN INDIA - Jain, Paras (International Journal of Research -GRANTHAALAYAH, 2017)
In the Indian context, the constitution makes envisaged a concept of social justice which involves the establishment of an egalitarian, social order where there was no discrimination among individuals on the basis of caste, religion, race, sex or place of birth. Goal of political, socio and economic democracy have been sought to be implemented through certain political and socio economic rights. These conditions were to be established by adopting a socio economic model of development through a policy of socialism. In present study year wise variation with respect to element of social justice is presented.